Investigation of structural and magnetic properties of Nd0.7Ba0.3Mn1-xTixO3 (x = 0.05, 0.15 and 0.25) manganites synthesized through a single-step process - Kumar D.; Singh A.K. (My University, 2025)
The polycrystalline Nd0.7Ba0.3Mn1-xTixO3 (x = 0.05, 0.15 and 0.25) perovskite manganites have been synthesized using combustion synthesis method followed by single-step calcination process. Rietveld analysis of the X-ray powder diffraction patterns reveals that the samples crystallize in single phase body-centered orthorhombic crystal structure with space group Imma. The lattice parameters and unit cell volume increase exponentially with doping of Ti4+ ions for Nd0.7Ba0.3Mn1-xTixO3 (x = 0.05, 0.15 and 0.25). The temperature dependence of magnetization measurements reveal that all samples undergo transition from paramagnetic (PM) to ferromagnetic (FM) phase on cooling below room temperature. The values of Curie temperature (TC), Curie-Weiss temperature (TCW) and experimental effective paramagnetic moment (μeff exp) decrease exponentially on the doping of Ti4+ ions. The field dependent magnetization measurements reveal coexistence of FM and antiferromagnetic (AFM) states in the low-temperature region. The experimentally observed saturation moment (μsat exp) of all the samples is lower than the theoretically calculated values and decreases exponentially with doping of Ti4+, due to AFM component in the FM ordering. The negative slope in the low field region of the M2 vs. H/M Arrott-plots for all the samples reveals that Nd0.7Ba0.3Mn1-xTixO3 manganites exhibit a first-order magnetic phase transition. The critical exponents β γ and δ were estimated for Nd0.7Ba0.3Mn1-xTixO3 perovskites. © 2018 Elsevier B.V.